Educational innovation and it’s impact on teachers - Páez Granja, Ruth Enriqueta (2020)
The purpose of this article is to analyze the processes of change and innovation in education and its impact on professors. The topic is relevant since higher education in Ecuador is going through an important transformation process that requires reviewing the curriculum content and the teaching methodology, key aspects that underlie any process of innovation or educational change and the adaptation of professors to these processes. The methodology consisted in the analysis of the main postulates of Fullan (2002-2012), Havelock and Huberman (1980), Rutherford and Hall (1990), Rogers (2003), Marcelo (1995-2010), among others, devoted to the impact of the processes of change in professors. As a result of this study, the proactive participation of teachers in the construction and strengthening of innovation processes is identified for the integral formation of citizens with a social and ethical commitment to the education at all levels. The work concludes with recommendations that implies the need to involve teachers from the beginning in the processes of educational transformation through awareness-raising, training and accompaniment programs.